The effectiveness of polyethylene oxide and calcium chloride in stabilization of former mine soil - 610457 Nor'Ashikin Aminudin, 1990- author; Nor Zurairahetty Mohd. Yunus supervisor 626642; Fakulti Kejuruteraan Awam 8022 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017